1996
DOI: 10.3354/cr007253
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of wheat simulation models under climate change. I. Model calibration and sensitivity analyses

Abstract: A comparison of the performance of 5 wheat models was carried out for 2 sites in Europe with considerably different agroclimatic conditions: Rothamsted, UK, and Seville, Spain. The models were calibrated against field data sets from both sites. For Rothamsted the measured time courses of crop growth, evapo-transpiration and nitrogen uptake were reproduced reasonably well by the different models, except for leaf area index. For Seville, the experimental data set was insufficient for such a detailed comparison a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(56 citation statements)
references
References 73 publications
3
53
0
Order By: Relevance
“…Models are often, but not always, calibrated. Experience has shown that even models that through calibration have been forced to achieve similar performance in a calibration period may exhibit quite different projections for future climates (Wolf et al 1996;Velázquez et al 2012).…”
Section: Projection Methodologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Models are often, but not always, calibrated. Experience has shown that even models that through calibration have been forced to achieve similar performance in a calibration period may exhibit quite different projections for future climates (Wolf et al 1996;Velázquez et al 2012).…”
Section: Projection Methodologiesmentioning
confidence: 99%
“…It is good practice in many earth science disciplines to conduct rigorous testing of models before they are applied for predictions (Jørgensen 1995;Refsgaard and Knudsen 1996;Wolf et al 1996). Such tests may be denoted validation tests, history matching or similar depending on the terminology used.…”
Section: Introductionmentioning
confidence: 99%
“…During seed-filling stage the oil and protein concentrations were inversely related in response to heat stress [94]. Pipolo et al [95] concluded similar quadratic response for oil and protein concentrations of soybean seeds cultured in vitro. A positive correlation was observed between protein and oil concentrations which was a function of rate of dry matter accumulation of soybean seeds.…”
Section: Effect Of Heat Stress On Plant Biochemistrymentioning
confidence: 97%
“…Increasing temperatures from optimum 25°C to 28°C, the oil content increased however, above 28°C the oil content declined [94]. In case of soybean seed protein content remained constant at temperatures between 16°C and 25°C but increased at temperatures above 25°C [94,95]. During seed-filling stage the oil and protein concentrations were inversely related in response to heat stress [94].…”
Section: Effect Of Heat Stress On Plant Biochemistrymentioning
confidence: 97%
See 1 more Smart Citation